Diabetes Mellitus and Hyperlipidemia Status Among Hypertensive Patients in the Community and Influencing Factors Analysis of Blood Pressure Control - Shijia Zhang; Yunou Yang; Xiongfei Chen; Liumei Fan; Jiagang Wu; Xiangyi Liu; Weiquan Lin; Zhiyu Zhai; Guozhen Lin; Hui Liu; Qin Zhou (The Journal of Clinical Hypertension)
Abstract To evaluate the prevalence of type 2 diabetes mellitus (T2DM) and hyperlipidemia in hypertensive patients in South China and assess the relationship between these comorbidities and blood pressure control to develop targeted strategies for hypertension management. Data from the 2020 Guangzhou National Basic Public Health Service Program were analyzed using Chi‐square tests, t‐tests, and logistic regression with R 4.1.2. Among 275,789 hypertensive patients, the blood pressure control rate was 51.51%. The prevalence of T2DM and hyperlipidemia comorbidities was 12.79%, with 12.78% for T2DM alone, 33.54% for hyperlipidemia alone, and 40.89% with no comorbidities. Blood pressure control rates significantly differed by comorbidity (p < 0.05): 52.84% for those without T2DM/hyperlipidemia, 54.18%, 49.25% for T2DM or hyperlipidemia alone, and 50.52% for both conditions. Multivariate analysis indicated a lower blood pressure control rate in patients with hyperlipidemia alone (OR = 1.144) or both T2DM and hyperlipidemia (OR = 1.082), and a higher rate in those with T2DM alone (OR = 0.936). Subgroup analysis revealed that males, older age, higher education, obesity, alcohol use, lack of physical activity, and poor medication adherence were associated with lower control rates. This study found a high prevalence of diabetes and hyperlipidemia among hypertensive patients in Guangzhou. Additionally, hypertensive patients with hyperlipidemia had poorer blood pressure control compared to other diabetic patients. Key factors such as obesity, being overweight, and unhealthy lifestyle choices significantly impact blood pressure management in this population. Therefore, comprehensive measures should be implemented to integrate lipid management into community health efforts and to effectively control blood pressure levels among hypertensive patients.